Relationship between Financial Performance and Ownership Structure on Sustainability Disclosure in SRI-KEHATI Index Firms - Anggarsari, Ayu; Prasojo (Journal of Accounting Inquiry, 2024)
Purpose: The purpose of this study is to analyze the effect of profitability, liquidity, profitability, institutional ownership, managerial ownership, and foreign ownership on the disclosure of sustainability reports. Methodology: This study uses a quantitative approach with panel data analysis. The sample selection used a purposive sampling technique and obtained 15 samples of companies listed in the SRI-KEHATI index from 2017-2021. Findings: The study results show that profitability, liquidity, institutional ownership, and managerial ownership do not affect the disclosure of sustainability reports. Foreign ownership has a negative effect on the disclosure of sustainability reports. Novelty: The novelty of this study is the research focus which analyzes the completeness of disclosing sustainability reports from companies with ESG principles, namely companies listed on the SRI-KEHATI index. In addition, the focus of the independent variables used is financial performance, which is proxied by profitability and liquidity, and ownership structure, which is proxied by institutional ownership, managerial ownership, and foreign ownership.